Faâ€™aliyyah IstikhdÄm KitÄb al-Lugah al-â€˜Arabiyyah al-Muá¹awwar fi á¸Œaui al-TakÄmul baina al-â€˜Ilm wa al-Wahy bi Qism al-RiyÄá¸iyyÄt wa al-â€˜UlÅ«m al-á¹¬abÄ«â€™iyyah bi JÄmiâ€™ah Sunan Gunung Jati al-IslÄmiyyah al-HukÅ«miyyah Bandung - Siti Sanah; M Abdul Hamid; Zulli Umri Siregar; Dedih Wahyudin (Arabic Education Program IAIN Pekalongan, 2021)
The purpose of this study was to measure the effectiveness of the use of Arabic textbook in improving the academic achievement of students from the Mathematics and Natural Sciences Department at the Tarbiyah Faculty of UIN Sunan Gunung Djati Bandung in the field of Arabic learning. The textbook was developed with Dick and Carey's development model that was adapted and modified by Lawrence Cunning Ham. Next, the textbook assessment was carried out with assessment instruments made by the National Education Standards Board (BNSP). This study used the quasi-experimental method with data obtained through pre-test and post-test and analyzed with T-test and Anova. The results of this study indicated that the average pre-test score of Arabic learning from Mathematics Education students was 37.00 (low), Physics Education 32.31 (low), Chemistry Education 33.17 (low), and Biology Education 28.53 (low). Meanwhile, the average post-test score of Arabic learning from Mathematics Education students was 79.74 (high), Physics Education 81.93 (high), Chemistry Education 80.43 (high), and Biology Education 81.72 (high). In general, students from the said departments experienced a high increase in the Arabic learning outcomes with an average increase of more than 0.70 (70%). This study implies that the use of a science-based textbook integrated with the verses of the Qur'an is very effective in improving academic achievement in Arabic subjects.